2022
DOI: 10.1186/s12903-022-02555-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic control and oral health in children with type 1 diabetes mellitus

Abstract: Background Type 1 diabetes mellitus is the most common chronic disease and can be reflected in the oral cavity. The aim of this study was to analyze the impact of metabolic control on saliva, dental caries, dental plaque, gingival inflammation, and cariogenic bacteria in saliva. Methods A case–control epidemiologic study was performed on children with type 1 diabetes (ages 10–15 years) separated into two groups: 34 children with good metabolic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
1
4
0
2
Order By: Relevance
“…The PD and dental caries were potentially higher in T1DM children with a lower level of oral hygiene, where brushing teeth was performed once a day and dental visit was commenced when necessary. [ 20 ] A similar finding of T1DM oral hygiene practice was found in an earlier study by Eldarrat[ 21 ], who reported mean toothbrushing frequency was only once daily, and 42% did not even floss. Another study reported similar toothbrushing frequency in T1DM and highlighted the practice level was even lower in adolescents (13–18 years).…”
Section: Introductionsupporting
confidence: 79%
“…The PD and dental caries were potentially higher in T1DM children with a lower level of oral hygiene, where brushing teeth was performed once a day and dental visit was commenced when necessary. [ 20 ] A similar finding of T1DM oral hygiene practice was found in an earlier study by Eldarrat[ 21 ], who reported mean toothbrushing frequency was only once daily, and 42% did not even floss. Another study reported similar toothbrushing frequency in T1DM and highlighted the practice level was even lower in adolescents (13–18 years).…”
Section: Introductionsupporting
confidence: 79%
“…Отже, поганий метаболічний контроль ЦД підвищує рівень впливу цих факторів [7]. Згідно з дослідженням A.A. Alavi та співавт., показники інтенсивності карієсу DMFT для дітей із ЦД становили 9,64 ± 4,64 і були вірогідно вищими порівняно з контрольною групою [8].…”
Section: поширеність та інтенсивність карієсу в дітей із цд 1-го типуunclassified
“…For example, studies of periodontal diseases in the context of diabetes have established a two-way relationship between T2DM and microbiome dysbiosis that is often the driving force behind deteriorating periodontal health [ 19 ]. For dental caries, there has been an increasing body of evidence associating poor glycemic control with increased risk for dental caries [ 20–25 ]. As such, more in-depth research is needed to address the impact of increased excretion of RES on microbial homeostasis in the context of dental caries.…”
Section: Introductionmentioning
confidence: 99%